SKORBA Excavations carried out on behalf of the National Museum of Malta 1961-1963 - Trump, D.H (Reports of the Research Committee of the Society of Antiquaries of London, 1966)
This is an account of the excavation of Li Skorba, in the north-west of the isle of Malta, which took place between 1961 and 1963. Included are descriptions of artefacts such as pottery, bone and buildings, together with an account of the methodology used to unearth these.